Women in God's Army: gender and equality in the early Salvation Army - Eason, Andrew Mark (Studies in women and religion, 2003)
Gender, stratification, and the sacred -- Ambiguous heritage : the Salvation Army's victorian and evangelical roots -- William Booth and women : settled views? -- Gendered geography : male Salvationists and women -- Catherine Booth : a public and domestic legacy -- Public and domestic service : the experiences of female officers.